Nutritional status and growth of children and adolescents with and without cerebral palsy in eastern Uganda: A longitudinal comparative analysis. - Lukia Hamid Namaganda; Carin Andrews; Fred Wabwire-Mangen; Stefan Peterson; Hans Forssberg; Angelina Kakooza-Mwesige (Public Library of Science (PLoS), 2023)
There is a need to understand the growth and burden of malnutrition in children with cerebral palsy (CP) in order to design appropriate inclusive nutrition strategies. We compared the nutritional status and four-year longitudinal growth of a population-based cohort of children and adolescents (C&A) with CP (n = 97; 2-17 years; 55/42 M/F), and an age and sex matched group without CP (n = 91; 2-17y; 50/41 M/F) in rural Uganda. The cohorts were assessed in 2015 and 2019 for weight, height, social demographic characteristics, and feeding related factors. Nutritional status was determined using the World Health Organization (WHO) Z-scores. Wilcoxon sign rank and Mann-Whitney tests were used to test within and between group differences. Multivariable linear regression was used to determine predictors of the change in growth. Approximately two thirds (62/97 (64%)) of C&A with CP were malnourished (with <-2SD in any of the WHO Z-scores), especially those with feeding difficulties (OR = 2.65; P = 0.032), and those who needed to be fed (OR = 3.8; P = 0.019). Both the CP and non-CP groups deviated negatively from the WHO reference growth curve for height, with a significantly slower growth in the CP group (median change score of height-for-age Z score (HAZ) between assessments = -0.80(-1.56, 0.31), p<0.01), than the non-CP group (median HAZ change score = -0.27(-0.92,0.34, p = 0.034). There was a statistically significant group difference in the median HAZ change score between the CP and non-CP groups (z = -2.21, p = 0.026). Severity of motor impairment measured by the Gross Motor Function Classification System (GMFCS-level) correlated negatively (r = -1.37,95%CI -2.67, -0.08) with the change in HAZ scores among the CP group. Children and adolescents with severe motor impairments exhibit an increased risk of malnutrition and growth retardation compared to their age matched peers without CP, which underscores the need to develop inclusive community-based nutrition strategies for children with cerebral palsy.